2019
DOI: 10.1021/jacs.8b11237
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Fragmentation of Cu2O Nanoparticles Enhancing Selective C–C Coupling from CO2 Reduction Reaction

Abstract: In this study, we demonstrate that the initial morphology of nanoparticles can be transformed into small fragmented nanoparticles, which were densely contacted to each other, during electrochemical CO 2 reduction reaction (CO 2 RR). Cu-based nanoparticles were directly grown on a carbon support by using cysteamine immobilization agent, and the synthesized nanoparticle catalyst showed increasing activity during initial CO 2 RR, doubling Faradaic efficiency of C 2 H 4 production from 27% to 57.3%. The increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
340
3
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 478 publications
(363 citation statements)
references
References 54 publications
18
340
3
2
Order By: Relevance
“…In stark contrast, electrochemical CO 2 reduction using renewable energy provides a cleaner and more sustainable route. Great effort has been made to develop efficient electrocatalysts toward C 2+ hydrocarbons (32,33,(65)(66)(67)(68)(69)(70).…”
Section: Multicarbon Hydrocarbonsmentioning
confidence: 99%
See 1 more Smart Citation
“…In stark contrast, electrochemical CO 2 reduction using renewable energy provides a cleaner and more sustainable route. Great effort has been made to develop efficient electrocatalysts toward C 2+ hydrocarbons (32,33,(65)(66)(67)(68)(69)(70).…”
Section: Multicarbon Hydrocarbonsmentioning
confidence: 99%
“…4E). To date, the active sites on copper have been identified as Cu 0 , Cu + , and/or their interface for ECR in different studies (39,41,42,81,82). However, what is the active site is still being debated.…”
Section: Multicarbon Hydrocarbonsmentioning
confidence: 99%
“…Later, Jung et al performed CO 2 RR studies with shape‐controlled Cu 2 O nanoparticles, and monitored the transformation of the catalyst. [ 75 ] HRTEM analyses showed that the Cu 2 O NPs with an initial particle size of 20 nm were slowly fragmented into 2–4 nm sized particles after 10 h of continuous CO 2 RR, and the CO 2 RR activity is highly related with the morphological changes. HRTEM images of catalysts at different elapsed time of CO 2 RR show that Cu 2 O catalysts collapsed and were fragmented into smaller sizes with compact arrangement and deformed crystal plane, as shown in Figure 4h,i.…”
Section: Surface Structure‐dependent Catalytic Activity/selectivity Omentioning
confidence: 99%
“…[15b] The designo fC u-based catalysts for practical and efficient CO 2 RR is still an ongoing issue. Recent advances in artificial rereduction from polluting Cu surfaces, including CuO, [32] Cu 2 O, [29,33] Cu 2 (OH) 3 Cl, [15c] CuO Cl , [15a] and boron dopedC u [15b] showed excellent C 2 + selectivity.A pplying these techniquest o well-defined Cu nanostructures, combined with variouso xidants for polluting Cu surfaces would be ap otential option to enhanceC 2 selectivity.T he monitoring of electrochemical CO 2 RR is also essential. Cu + residues during the electrochemical CO 2 RR promote C 2 + production, and factors such as the density of defects, the types of dopants, and the surface morphologies are strongly correlated with the maintenance of Cu + species.H owever,t he precise state of Cu + species and the mechanism of CÀCc ouplingo nC u + surfaceh ave not been resolved yet.…”
Section: Cu Nanoparticles For Hydrocarbon Productionmentioning
confidence: 99%
“…The resulting catalyst showed al arge increaseo fe thylene Faradaic efficiency,u pt o5 4% after 6h at À1.1 V(vs. RHE). [33] Although the FEs for C 2 chemicals in electrochemical CO 2 RR were highlye nhanced by various types of catalyst design, the exact formation mechanism is still unclear.Ah igh local pH is one of the reasons for high Fes because it promotes the CÀC coupling reaction. However,a no verly-high pH condition hasa negative effect of reducing CO 2 solubility in electrolytes.…”
Section: Cu Nanoparticles For Hydrocarbon Productionmentioning
confidence: 99%